Tiger beetle fauna (Coleoptera: Carabidae, Cicindelinae) of Morocco: distribution, phenology and list of taxa - Jaskuła, Radomir; Rewicz, Tomasz; Kwiatkowski, Kajetan (Entomologica Fennica, 2015)
The diversity and distribution of Cicindelinae in Morocco, including new unpublished data, is summarized and discussed. In total 17 species are reported from the country. Cicindela campestris campestris is excluded from the Moroccan fauna while the occurrence of Myriochila mirei is doubtful and should be confirmed by new data. The area adjacent to the Mediterranean Sea and Atlantic Ocean coastlines holds the highest species diversity, while mountainous regions are characterized by lower diversity but also by high level of species endemism. Grouped on the basis of their chorotypes, Moroccan Cicindelinae fall into six different groups: West Mediterranean (44% of Cicindelinae species), Maghreb endemics (22%), Mediterranean (11%), Saharian (11%), Mediterranean-Westturanian (6%) and Afrotropico-Indo-Mediterranean (6%). According to their phenology, the Moroccan tiger beetles can be divided into three groups: 1) spring active species, 2) spring-summer active species, and 3) summer active species.